Correlating maternal iodine status with neonatal thyroid function in two hospital populations in Ghana: a multicenter cross-sectional pilot study - Selorm A. Dei-Tutu; Adoma Manful; Douglas C. Heimburger; Hawa Malechi; Daniel J. Moore; Samuel A. Oppong; William E. Russell; Muktar H. Aliyu (BMC, 2020)
Abstract Background Congenital hypothyroidism is a common, yet easily treatable cause of poor growth and intellectual disability. Newborn screening programs play an important role in the early detection and treatment of congenital hypothyroidism. However, an estimated 71% of children are born in countries such as Ghana, which does not have a screening program. Iodine deficiency, a common cause of congenital hypothyroidism, is present in the Ghanaian population. Mild to moderate maternal iodine deficiency may negatively impact cognitive function in children. A structured approach to examine the association between maternal iodine levels and infant thyroid function may have important ramifications on our understanding of congenital hypothyroidism in Ghana. We investigated the hypothesis that maternal iodine deficiency impacts infant thyroid function, using Thyroid Stimulating Hormone (TSH) as a marker of thyroid function. We also explored potential opportunities and barriers to newborn screening for congenital hypothyroidism in Ghana. Methods This was a cross-sectional, multicenter pilot study of 250 women and their neonates recruited from post-natal clinics in Accra and Tamale, Ghana. We compared maternal urine iodine concentration and infant TSH, as well as maternal sociodemographic and nutrition information. Regression models were used to model the relationship between variables. Results Median infant TSH was 4.7 μIU/ml (95% CI: 3.9-5.5) in Accra. In Tamale, the median infant TSH was 3.5 μIU/ml (95%CI: 3.3 to 3.6) (Δ: 1.3 μIU/ml, 95% CI: 0.5-2.1, p = 0.002). Median maternal urine iodine concentrations were 141.0 μg/L (95% CI: 115.7 to 166.3) and 142.5 μg/L (95% CI: 125.1 to 160.0) in Accra and Tamale, respectively (Δ: − 1.5 μIU/ml, 95% CI: − 32.2 - 29.2, p = 0.925). There was a weakly positive correlation between maternal urine iodine and infant TSH (rho 0.1, p = 0.02). Almost one-third (30%) of women in both locations had biochemical evidence of iodine deficiency. Mothers with any formal education were more likely to have higher iodine levels than their counterparts who had no formal education (coefficient 0.31, p = 0.006). Conclusions Maternal iodine deficiency is prevalent in Ghana and is correlated to infant thyroid function. We recommend studies with larger sample sizes to assess the true scope of this relationship.